Delayed implants sepsis in HIV-positive patients following open fractures treated with orthopaedic implants. Issue 4 (April 2015) - Phaff, Martijn; Aird, James; Rollinson, P.D.
Abstract: Background: There has been concern that HIV-positive patients may be more susceptible to delayed infection (>1 month) after treatment of open fractures with orthopaedic implants. To date, the longest published follow-up for such patients is 6 months. Aim: Long-term follow-up to identify rates of delayed implant sepsis in open fractures treated with internal fixation, in HIV positive patients and controls. Methods: Prospective observational study. Between March 2011 and April 2012, we attempted to contact all patients who were enrolled into a study looking at outcomes of open fractures treated with internal fixation between May 2008 and March 2009. Telephone questionnaires were used to screen for implant sepsis, and patients received clinical assessments at our research clinic. Results: Of 101 patients with in situ implants, we were able to follow 51 patients. Of the initial 33 HIV-positive patients, 13 were reassessed as part of this study. Only 1 of 13 HIV-positive patients developed delayed implant sepsis following a grade 3B open tibia fracture. Two of 23 HIV-negative patients developed delayed implant sepsis. Conclusion: With an average follow-up period of 39 months (range = 34–43 months), this is the longest follow-up period to evaluate HIV-positive patients with open fractures who received orthopaedic implants. Despite its limitations of poor follow up, it provides the strongest available evidence that in our setting HIV positive patients are not at higher risk of delayed sepsis, and we would not suggest routine removal of metal work in these patients.